234k views
4 votes
Choose the definition for the function.

(-2x + 1 x ≤ 1
2 x>1
a.y=-x+ 2
-x+
b.y = -x + 2
-x+
{
(-2x + 1 x < 1
x ≥1
2
c.y =
(-2x + 1 x > 1
x≤1
-x+2
(-2x + 1 x ≥ 1
-x+ 2 x < 1
d. y = {-2x+1

Choose the definition for the function. (-2x + 1 x ≤ 1 2 x>1 a.y=-x+ 2 -x+ b.y-example-1
User Amal Ajith
by
4.8k points

2 Answers

7 votes

Answer: The answer is B

Explanation:

I currently don't have time to copy my paper onto this, I will edit this when I get the time.

User Nitesh Tarani
by
4.4k points
4 votes

Answer:

a

Explanation:

The part of the graph with equation y = -2x + 1 has an open circle at x = 1.

  • Eliminate b, c, d.

This leaves a as the correct answer.

User Nathan Marotte
by
4.1k points